Da'wah Amongst Secular Communities: Case Study on Al-Falah Mosque Indonesian Society, Berlin - Yusuf, M. Yunan (LPPM IAIN Kudus, 2017)
As the capital city of the Federal Republic of Germany, Berlin shows shades of very thick secular life. Society perceives that religious or supernatural beliefs are not considered as key understanding the world. Therefore, religion must be separated from issues of government and public affairs. It simply seen as merely an individual problem. Inevitably the nuances of life, it will affect Indonesian who are followers of Islam in Berlin. They will be a challenge, especially the Moslem communities who interact with fellow Moslems in maintaining Islamic values is very rarely. In addition, it also felt the rise of individualism attitude that emphasizes life nafsi-nafsi among themselves. This obviously affects the religious belief that a bit much degraded in consciousness and its practice. To overcome this, Al-Falah Mosque Indonesisches Weisheitits-und Kulturzentrum (IWKZ) Berlin proselytizes enlightening discussion. These da’wah activities carried out can stem the influence of secular life faced by Indonesian who are Moslem in Berlin.